Birmingham Medical Research Expeditionary Society 1977 Expedition: the diuresis and related changes during a trek to high altitude. Issue 645 (July 1979) - Howell, A.; Cove, D. H.
Abstract : Continuous 24-hr urine collections were made by 17 subjects during a trek to 5400 m. Fluid intake was recorded by diary. Weight and fat folds were measured daily. The results were compared with daily measurements of packed cell volume (PCV) and reticulocyte count. Early fluid retention was matched by a fall in PCV. There was a diuresis with negative fluid balance towards the end of the ascent and again early in descent. There was a slight trend for fluid retention to occur in those most affected by acute mountain sickness but the effect was not marked.